MODERN METHODS OF TEACHING THE TRIGONOMETRY SECTION OF MATHEMATICS IN GENERAL SECONDARY SCHOOLS - Feruz Sanakulovich Aktamov; Soatmurotov Xumoyun Alimardon o’g’li (Galaxy International Interdisciplinary Research Journal, 2022)
The study of trigonometric problems is not limited to the scope of one school subject, because they reflect a much wider field of human life, include real and potential infinity, continuity and spaces. School students should have a strong knowledge of trigonometry because. they are part of a chain of large networks and have a large network in the implementation of inter-objective communication. Studying the process of trigonometry in high school is associated with a number of productions: high levels of abstraction of problems, complex logical structure of software definitions, study time to understand the complexity of problems, etc.